Sistem Pendukung Keputusan Penentuan Sanksi Disiplin Bagi Siswa di SMP Kristen Makedonia Ngabang Menggunakan Metode Simple Multi Attribute Rating Technique (SMART) - Mardonius Wandi Pratama; Albert Yakobus Chandra (Universitas Mercu Buana Yogyakarta, 2023)
Discipline is very important in supporting school rules and regulations that must be obeyed by every student. Even with the existing rules, there are still students who violate these rules. With this, the school makes sanctions for violations that can have a deterrent effect on students so they don't violate school rules. Macedonia Ngabang Christian Middle School is one of the schools that has implemented sanctions against student discipline. However, for the provision of disciplinary sanctions, guidance and counseling (BK) teachers still experience problems in determining the appropriate disciplinary sanctions for students based on the violations committed. There are many methods that can assist in building a decision support system in determining disciplinary sanctions for students who violate school rules, one of these methods is the Simple Multi Attribute Rating Technique (SMART) method. The SMART method is the right method for this research because it can determine the sanctions for violations based on criteria and sub-criteria based on predetermined weights. With a decision support system, it can help guidance and counseling teachers and teachers who teach in schools in determining appropriate disciplinary sanctions against students who violate school rules and regulations.